PELAKSANAAN EVALUASI PAI BERBASIS CBT (COMPUTER BASED TEST) DI MA DARUTTAUHID MALANG - Firsta Pramudita Utomo Putra; Anwar Sa'dullah; Abdul Jalil (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The first step of the PAI evaluation is the teacher collects the test questions file to the exam proctor, the exam proctor is the one who regulates and safeguards all computer-based examination activities, then the student runs the test as explained by the examination committee. The effectiveness and results of computer-based examinations are that the teacher gets the evaluation results from the CBT committee team much faster and precisely, namely when the exam has taken place and the assessment system runs automatically, the evaluation process is more effective, precise, fast and valid. And the last of the objectives of this study is to know the obstacles that exist in CBT-based exams, barriers are divided into two, namely internal barriers and external barriers. Internal barriers for example are: lack of computer units, low quality computers, less than optimal space. External barriers are: unstable internet network, power outages, images on questions sometimes less clear.Keywords: Implementation, evaluation, Computer Based Test, PAI